The Polemic of Shahjahanpur: Religion, Miracles, and History - Tareen, SherAli (Islamic Studies, 2012)
This essay analyzes the content and context of a major inter-religious polemic held in the North Indian district of Shahjahanpur in 1875 and 1876: “The Festival of Deciding the [True] God (Mailah-i Khuda Shinasi).” This polemic brought together leading Hindu, Muslim, and Christian missionary scholars in India, as they debated and contested the authenticity of their respective doctrinal systems. It was organized through the patronage of the British magistrate’s office in Shahjahanpur. The renowned Muslim scholar and founder of the prestigious Deoband seminary Qasim Nanautvi (d. 1877) and the acclaimed Hindu reformer and founder of the Arya Samaj Dayananda Sarasvati (d. 1883) were among the most prominent scholars who attended this polemical spectacle. In this essay, I examine the Shahjahanpur polemic from the perspective of Deoband┘ historiography and focus on the discourses of Qasim Nanautvi, especially on the question of prophetic miracles. Through a close reading of Nanautvi’s arguments for the superiority of Prophet Muhammad’s miracles over those of other Prophets, I raise and address larger questions about the relationship between native religious polemics, colonialism, and secular modernity in late nineteenth.